From Superantigens to “Real” Viral Antigens - Blackman, Marcia A. (Viral Immunol, 2020)
Studies inspired by Dr. Peter Doherty led to over 16 years of research into the mouse gamma-herpesvirus, γHV68, in the Blackman laboratory. Progress on our understanding of γHV68 biology include insight into the establishment of latency, immune control of the acute and latent stages of infection and experimental vaccines, is described here.